Efeitos da intervenção com exercícios físicos no ambiente de trabalho sobre o tempo de reação e o humor - Laux, Rafael Cunha (2016)
The program with physical exercises in the work environment is a tool used to minimize work-related illnesses. There are studies showing that this program helps to reduce absenteeism, muscle pain and repetitive-efforts illnesses, however, there is almost no research with reaction time and mood. Based on this scenario, the objective is to evaluate the effects of an intervention with physical exercise in the work environment in the reaction time and mood of administrative technical servers. The study is characterized as experimental and non-probabilistic. The research population was composed by 75 employees, from administrative sectors, between 18 and 50 years, of the Universidade Federal da Fronteira Sul - Campus Chapecó. The study group of the article of reaction time was composed by 26participants with an average age of 29,62±6,47 years and the study group of the mood article was composed by 25 participants with an average age of 32,16±9,64 years. The simple reaction and choice times were evaluated using the Vienna Test System and the mood was evaluated using the Brunel mood scale. The chronic effect of the physical exercise intervention in the workplace environment on the reaction time was evaluated after a program of 36 sessions, distributed 3 times a week for 12 weeks, totaling 6 hours of intervention. The acute effect of the physical exercise intervention in the work environment on the mood state was evaluated pre and post session of 10 minutes of the program.For the data treatment, descriptive statistics (average and standard deviation) and inferential analysis were used. All analyzes were performed at a significance level of 5%. The results of the article "The improvement of the reaction time after an intervention with physical exercises in the work environment" indicates decrease in the simple reaction and choice times, in the time of movement and in the time of response of the experimental group. The article "Acute effect of a session of workplace physical activity on mood state " has observed decrease of all negative aspects of mood, tension, depression, anger, fatigue and mental confusion. It was concluded that the intervention program with physical exercise in the work environment improved the simple reaction and choice times and the mood of the administrative staff.